The Expression of CXCR4 and MMP13 in Colorectal Adenocarcinoma Dukes Stage A, B, C and D - Anggoro, Rovi; Kusumastuti, Etty Hary (Indonesian Journal of Cancer, 2018)
Background: Colorectal adenocarcinoma is the third most common cancer in the world with increasing incidence in Indonesia. Most presented ones were in late stage with more unfavorable prognosis. It is necessary to evaluate new markers for prognosis, identify staging and new possibilities for targeted therapy. Over-proliferating tumor cells will enhance the expression of CXCR4, a chemokine receptor. Activating CXCR4 will further activate various downstream signaling pathways, including one which will increase MMP13 secretion through MAPK/ERK signaling pathway. MMP13 then will degrade extracellular matrix, thus facilitate the migration or metastasis of tumor cells. Methods: A cross sectional study, conducted on 32 samples of colorectal adenocarcinoma. The samples were divided into four groups based on the Dukes staging system (A, B, C and D) and stained immunohistochemically with antibody against CXCR4 and MMP13. The expressions were assessed using immunoreactive score (IRS) and were statistically analyzed. Results: There were positive correlation between the expression of CXCR4 and MMP13 with Dukes staging, with rs = 0,628 and rs = 0,597, respectively. The expression of CXCR4 positively correlated with the expression of MMP13 with rs = 0,670 (p = 0,05). Conclusions: CXCR4 and MMP13 expressions were proven to correlate with the depth of invasion and migration of tumor cells in colorectal adenocarcinoma, hence could be considered as prognostic markers, however both could not be used as predictive marker for staging. Tailored therapies targeting these two proteins could be an interest for further investigation. ABSTRAKLatar Belakang: Adenokarsinoma kolorektal adalah keganasan terbanyak ketiga di dunia, dengan insidensi semakin meningkat di Indonesia. Sebagian besar kasus terdeteksi pada stadium lanjut dengan prognosis buruk. Diperlukan penemuan marker baru yang dapat membantu penentuan stadium, prognosis dan kemungkinan terapi target yang baru. Sel tumor yang berproliferasi berlebihan akan menyebabkan peningkatan ekspresi CXCR4, suatu reseptor kemokin. Aktivasi CXCR4 akan meningkatkan pelepasan proteinase MMP13 melalui jalur MAPK/ERK. MMP13 akan mendegradasi matriks ekstraseluler sehingga menyebabkan migrasi atau metastasis sel tumor. Metode: Studi cross sectional, dilakukan pada 32 sampel adenokarsinoma kolorektal. Sampel dibagi menjadi 4 grup; stadium Dukes A, B, C dan D. Dilakukan pulasan imunohistokimia dengan antibodi CXCR4 dan MMP13, ekspresi keduanya dinilai menggunakan immunoreactive score (IRS) dan dianalisis secara statistik. Hasil: Didapatkan korelasi positif bermakna antara ekspresi CXCR4 dan MMP13 dengan stadium Dukes, dengan rs = 0,628 dan rs = 0,597. Ekspresi CXCR4 berkorelasi positif dengan ekspresi MMP13 dengan rs = 0,670 (p = 0,05). Kesimpulan: Ekspresi CXCR4 dan MMP13 terbukti berkorelasi dengan kedalaman invasi dan migrasi sel ganas pada adenokarsinoma kolorektal. Keduanya dapat dipertimbangkan sebagai marker prognostik namun tidak dapat digunakan sebagai marker prediktif stadium. Targeted therapy untuk kedua protein ini menarik untuk dilakukan investigasi lebih jauh.